2001
DOI: 10.19182/remvt.9771
|View full text |Cite
|
Sign up to set email alerts
|

Prévalence des lésions tuberculeuses pulmonaires chez le bétail

Abstract: Une enquête sur la tuberculose chez le bétail a été réalisée dans quatre abattoirs situés à Maiduguri, Damboa, Damaturu et Gashua au nord-est du Nigeria, de 1994 à 1998. Sur un total de 1 698 000 bovins abattus examinés post mortem, 2,8 (intervalle de confiance de 95 p. 100 : 2,76–2,84) avaient des lésions tuberculeuses pulmonaires. La prévalence a varié de 1,9 p. 100 à l’abattoir de Damaturu à 20 p. 100 à celui de Damboa. Les prévalences annuelles durant la période de l’étude ont varié de 2,3 à 4,7 p. 100. Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Conventional mycobacteriological methods are often unsafe in inadequately constructed and poorly equipped laboratories (Igbokwe et al 2001), common in most of Africa. Such methods are also expensive, time consuming, laborious and not practical for surveillance purposes (Strong and Kubica 1985;Grange et al 1996;Parsons et al 2002;Warren et al 2006).…”
mentioning
confidence: 99%
“…Conventional mycobacteriological methods are often unsafe in inadequately constructed and poorly equipped laboratories (Igbokwe et al 2001), common in most of Africa. Such methods are also expensive, time consuming, laborious and not practical for surveillance purposes (Strong and Kubica 1985;Grange et al 1996;Parsons et al 2002;Warren et al 2006).…”
mentioning
confidence: 99%
“…The 1.76% prevalence of tuberculosis in the present study was comparable to the reported prevalences of 1.1% in Maiduguri (Raufu and Ameh, 2010) and 1.9% in Makurdi (Ejeh et al, 2014a), in Nigeria. It was, however, relatively lower than those of 2.8% (Igbokwe et al, 2001), 4.05% (Aliyu et al, 2009) and 2.9-6.5% (Ejeh et al, 2014b) reported in areas of Northern Nigeria. These differences may be associated, on one hand, with climatic conditions that facilitate bovine tuberculosis persistence and transmission, as they vary from north to south of Nigeria depending on the geographical location, and, on the other hand, with the methods of diagnosis of positive cases.…”
Section: ■ Results and Discussionmentioning
confidence: 58%
“…In Bauchi State, for instance, a prevalence of 15%, 29.16% and 8.33% by post-mortem, Ziehl-Neelsen and Polymerase Chain Reaction (PCR), respectively, was reported [12]. A study conducted in 2018 [13] at selected abattoirs in Bauchi and Gombe States reported the prevalence of bovine tuberculosis to be 9.8% and 13.9%, respectively, while a 5-year retrospective study in Adamawa State, Northeastern Nigeria reported a prevalence of 6.7% [14] and this was higher than the prevalence of 0.34% reported in 2009 [15] for Adamawa State and 2.8% for Damaturu (Yobe State), Maiduguri and Damboa (Borno State) in 2001 [16]. An overall prevalence of 8.2% of bovine tuberculosis was reported in Rivers State, Southern Nigeria in cattle slaughtered in the University of Portharcourt central abattoirs where M. bovis was confirmed to be the causative agent of lesions observed [17].…”
Section: Introductionmentioning
confidence: 98%